Computer simulation and analysis of hemodynamic changes in abdominal aortic aneurysms treated with fenestrated endovascular grafts - Sun, Zhonghua; Chaichana, T.; Sangworasil, M.; Allen, Yvonne; Hartley, D.; Lawrence-Brown, M. (ISBME, 2008)
The purpose of this study was to perform a simulation of blood flow and analyze the hemodynamic changes in patients with abdominal aortic aneurysms (AAA) treated with fenestrated stent grafts. Four patients with AAA undergoing multislice computed tomography angiography pre-and post-fenestrated stent graft implantation were selected for inclusion in the study. Geometric models and hexahedral volume meshes were successfully generated for pre- and post-stent fenestrated implantation. The blood flow pattern was simulated inside the abdominal aortic aneurysm and arterial branches, as well as with a stentgraft in situ. Flow visualization showed that flow disturbances inside the aneurysm were apparently decreased and flow rate was not affected significantly at the renal arteries after deployment of the fenestrated stents intothese branches. The wall pressure was found to reduce inside the aneurysm sac following implantation of stent grafts. In this preliminary study, we successfully simulated the flow characteristics in abdominal aortic aneurysm before and after fenestrated endovascular repair.